Developing an Arabic Language Curriculum through a Reflective-Metacognitive Learning Approach - Zailani Novian; M. Royan Firdaus; Siska Qurrota A'yun; Talitha Rahma Azzahra; Muhajir (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2026)
This study aimed to develop an Arabic language curriculum based on the Reflective–Metacognitive Learning (RML) approach to enhance students’ self-awareness and learning autonomy. Employing a qualitative descriptive design through library research and content analysis, the study examined theoretical frameworks and formulated curriculum components that integrate reflective and metacognitive principles. The results revealed that RML encouraged students to plan, monitor, and evaluate their learning consciously, transforming classroom instruction into a learner-centered process. The model emphasized reflective journals, guided discussions, and self-evaluation as part of the curriculum design. This approach provided teachers with practical references for integrating reflective–metacognitive strategies into Arabic learning and contributed to curriculum development aligned with 21st-century educational goals.